2021
DOI: 10.1186/s12957-021-02414-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical analysis of metastatic characteristics of infrapyloric lymph nodes (No.206) and terminal ileum lymph nodes in patients with right colon cancer

Abstract: Background D3 or complete mesocolic excision (CME) surgery has become a common surgical procedure for the treatment of colon cancer metastasis. Clinical misuse and overuse of lymph node dissection bring unnecessary burdens to patients. A detailed guidance for lymph node dissection in patients with T3 and T4 stage right colon cancer at different locations is urgently needed. Methods A retrospective study was performed. Patients received D3 or CME su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…The sample size was calculated using the primary endpoint. According to previous studies,12 14–16 18 19 21 26 27 our hypothesis is that the metastasis rate of No. 206 and No.…”
Section: Methods and Analysismentioning
confidence: 89%
See 2 more Smart Citations
“…The sample size was calculated using the primary endpoint. According to previous studies,12 14–16 18 19 21 26 27 our hypothesis is that the metastasis rate of No. 206 and No.…”
Section: Methods and Analysismentioning
confidence: 89%
“…206 LN metastases are related to tumour location (p=0.019) and degree of differentiation (p<0.001). 21 There are some limitations in previous studies. First, all studies were single-centre, retrospective studies with a limited sample size.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The researchers did not provide information about the length of the dissected terminal ileum. However, they performed extended resection of the terminal ileum in cecum cancer patients [ 16 ]. Baik et al reported that 10 cm ileum resection would be sufficient in patients with cecum cancer [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…5 Liu et al reviewed the literature on metastases of right colon cancers to peri-ileal LNs and found that 3.2% of these patients had metastatic peri-ileal LNs, among which caecal cancer had the highest metastatic rate (8.2%) compared to ascending (2.6%) and hepatic flexure (1%) colon cancer. 6 In these studies, the surgeons consciously tried to resect a longer portion of the terminal ileum in caecal cancer patients.…”
Section: Introductionmentioning
confidence: 99%